2008
DOI: 10.1086/593211
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic and Case‐Control Study on Hepatitis E Virus Infection in Germany

Abstract: Background. Hepatitis E is a classic water-borne disease in developing countries. In Germany, hepatitis E virus (HEV) infections are notifiable. The number of non-travel-associated infections has increased in recent years, but the route of transmission in most is unknown. Our objective was to determine risk factors for autochthonous HEV infections in Germany.Methods. Cases of HEV met clinical definitions and were confirmed by laboratory analysis (defined as detection of HEV by polymerase chain reaction [PCR] … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
277
1
9

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 263 publications
(299 citation statements)
references
References 31 publications
12
277
1
9
Order By: Relevance
“…In Germany, the consumption of offal, such as pig liver and parts of wild animals (wild boar), was associated with native infections by HEV (Wichmann et al, 2008). Similar cases were reported from the consumption of venison with HEV in Japan (Tei et al, 2003).…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…In Germany, the consumption of offal, such as pig liver and parts of wild animals (wild boar), was associated with native infections by HEV (Wichmann et al, 2008). Similar cases were reported from the consumption of venison with HEV in Japan (Tei et al, 2003).…”
Section: Discussionsupporting
confidence: 55%
“…Pig liver is a common dietary component in many countries and is used as an ingredient in sausages or is grilled for consumption. In Germany, pig liver consumption was associated with HEV infection in a case study (Wichmann et al, 2008). Additionally, the consumption of raw sausages containing pig liver was identified as the probable source of an HEV infection in France (Colson et al, 2010).…”
Section: Introductionmentioning
confidence: 95%
“…In a risk factor EL2 analysis using a structured questionnaire, dried sausages and uncooked shellfish (mussels, oysters, or both) were considered risk factors associated with cases in The Netherlands and France, respectively, but these studies did not use controls [19,51]. In the EL3 case-control study in Germany, Wichmann et al found that eating any offal or wild boar was independently associated with autochthonous HEV infection [52]. No significant association was found for other food products from other animals including shellfish.…”
Section: Potential For Foodborne Zoonotic Transmissionmentioning
confidence: 99%
“…In the EL2 enhanced surveillance conducted by Borgen et al in The Netherlands it was specifically asked if any family members or close contacts had signs of hepatitis in the months preceding or following the disease period of the cases, but no positive responses were elicited and a limited contact investigation found no evidence of HEV infection [19]. During the enhanced surveillance conducted for the case-control study in Germany, unstructured household investigations identified five additional IgM-positive HEV cases in three households of autochthonous cases [52], one of whom was PCR-positive. All were asymptomatic or complained only of mild abdominal pain or fatigue.…”
Section: Potential For Other Transmission Routes and Risk Factorsmentioning
confidence: 99%
“…3 At least five different HEV genotypes have been described, with four of them being able to infect humans. HEV genotype 3 has frequently been associated with zoonotic infections, 4,5 whereas HEV genotypes 1 and 2 appear to primarily infect humans. We recently confirmed the anthropo-zoonotic capacity of HEV genotype 3 by experimentally infecting pigs with a serum sample of a chronic HEV-infected patient.…”
mentioning
confidence: 99%